Engineering nanozymes for theranostics in urological cancer - Zhang, Xiangyu; Jiang, Yongnan; Liu, Bin; Yu, Xinlu; Jia, Bo; Dong, Yulong; Gu, Xinquan; Xue, Jinru; Fan, Kelong; Zhang, Yuhan (Nano today, 2026)
Urological malignancies are highly prevalent and lethal, with recurrence, late diagnosis, and therapeutic resistance compromising patient survival and quality of life. To address these challenges, tumor microenvironment (TME)-responsive strategies—particularly nanozyme-based catalytic systems—have emerged as promising solutions. Cascade catalytic nanozymes can be selectively activated within the TME to generate reactive oxygen species (ROS) through sequential enzyme-mimicking reactions. Moreover, they catalyze the depletion of intracellular antioxidants, amplifying oxidative stress and enhancing redox-driven therapeutic efficacy. These processes induce regulated cell death pathways such as ferroptosis and cuproptosis while reinforcing tumor immunogenicity. In addition, certain metal-based nanozymes act as imaging contrast agents, integrating diagnosis and therapy within a single platform. The diagnostic potential extends beyond traditional imaging and tissue assays, with urine emerging as a valuable, non-invasive biofluid for complementary analysis. This review summarizes recent progress in nanozyme-based catalytic nanomedicine for urological cancers, focusing on cascade catalytic mechanisms, material design, and multifunctional theranostic applications. Finally, the challenges and future directions of intelligent, urine-compatible, imaging-assisted, and clinically translatable nanozyme systems are discussed toward precision urologic oncology.